Peningkatan Kualitas Pendidikan melalui Pengelolaan Kesiswaan Berdasarkan Instrumen IASP 2020 dalam Perspektif Manajemen Strategik : Studi kasus di MIN 1 Kota Bandung - Fina Ariatpi; Mulyawan Safwandy Nugraha (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
This study aims to analyze the implementation of student management based on the 2020 Education Unit Accreditation Instrument (IASP) from a strategic management perspective at MIN 1 Bandung City. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and document analysis. The results showed that the implementation of student management based on IASP 2020 has improved the quality of education at MIN 1 Bandung City, with significant improvements in the aspects of students' academic and non-academic achievements, as well as the effectiveness of character development programs. However, there are still challenges in terms of optimizing the student management information system and parental involvement. This study provides theoretical and practical contributions in developing effective student management strategies at the madrasah ibtidaiyah level.